Advertisement

Advertisement

Advertisement

Sum

**Solve the following :** `int_0^1 e^(x^2)*x^3dx`

Advertisement

#### Solution

Let I = `int_0^1 e^(x^2)*x^3dx`

= `int_0^1 e^(x^2)*x^2*xdx`

Put x^{2} = t

∴ 2x·dx = dt

∴ x·dx = `(1)/(2)*"dt"`

When x = 0, t = 0

When x = 1, t = 1

∴ I = `(1)/(2) int_0^1 e^"t"*"tdt"`

= `(1)/(2){["t" int e^"t"*"dt"]_0^1 - int_0^1[d/"dt" ("t") int e^"t"*"dt"]"dt"}`

= `(1)/(2) [["t"*e^"t"]_0^1 - int_0^1 1*e^"t" "dt"]`

= `(1)/(2){(1*e^1 - 0) - [e^"t"]_0^1}`

= `(1)/(2)[e - (e^1 - e^0)]`

= `(1)/(2)(e - e + 1)`

∴ I = `(1)/(2)`.

Concept: Fundamental Theorem of Integral Calculus

Is there an error in this question or solution?